Vitamin D – a novel role in pregnancy - Arora Chander, P.; Hobel, C.J. (Вiopolymers and Cell, 2010)
Vitamin D regulates placental development and function. It is a potent regulator of the immune system- stimulating antimicrobial responses while suppressing inflammation. Its deficiency has been linked to increased risk of serious chronic and inflammatory diseases. Vitamin D deficiency during pregnancy increases susceptibility to infection and inflammation, leading, in turn, to outcome like preterm birth or preeclampsia. Pregnant women with darker skin pigmentation are more likely to be vitamin D deficient, particularly when living in regions with low exposure to sunlight. It is possible that during pregnancy, a primary non-infectious inflammatory process is activated by vitamin D deficiency. Combined assessment of vitamin D deficiency and inflammatory markers in early pregnancy or during different stages of pregnancy may facilitate the recognition of the risk of complications.